Validitas LKPD dan Video Pembelajaran Materi Operasi Hitung Bentuk Aljabar Berbasis Pendekatan PMRI dengan Konteks Kantin Sekolah - Elisyah, Nur; Hidayatsyah, Hidayatsyah; Amam Taufiq Hidayat (Indo-MathEdu Intellectuals Journal, 2024)
Algebra is a very important material to study because algebraic concepts are widely used in subsequent material and are useful in solving mathematical problems in everyday life. The aim of this research is to determine the validity of LKPD and learning videos on algebraic arithmetic operations based on an Indonesian realistic mathematics education approach. The research method used is development research developed by Tessmer with two stages, namely the preliminary stage (analysis and design) and the formative evaluation stage (self evaluation, expert review, one to one, small group, and field test. In this research the focus is on the formative evaluation, one of which is an expert review. From the results of the validation carried out by the expert review, an average assessment percentage of 76.11% was obtained with the criteria being quite valid or usable with slight revision. The validation assessment indicators are content, construct and language